Շփմաև մեջ կոնֆլիկտային տարրերի հոգեբանական առանձնահատկությունները - Հայկ Թադևոսյան (ՀՀ ԳԱԱ հրատ.)
In the article the topic is touched upon that the conflicts can be handled at general social level, at communicative and interpersonal levels. The Analysis of conflicts during communication makes possible to develop communicative skills by means of which it becomes easy and effective. Such communicative skills are also used by solving conflictive situations, as through verbal "techniques" it becomes possible to change the whole essence of the phenomenon.
Keywords: Philosophy; Psychology; Religion; Psychology